Effectiveness of Professional Development Programs in Indonesia: A Survey of Educators’ Perspectives on Training and Support - Tupamahu, Marissa Swanda; Imanuela Trifosa Pietersz; Chiyene Trinie Dhea Suryana; Priska Zafanya Rembang; Alfa Alan Jackson Atty (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study examines the effectiveness of professional development (PD) programs in Indonesia from educators’ perspectives, focusing on training quality, content relevance, implementation, and follow-up support. Using a descriptive quantitative research design, data were collected from 47 teachers across eight junior and senior high schools in Sorong City through a structured questionnaire. The results indicate that PD programs are highly beneficial in enhancing teachers’ knowledge, introducing innovative teaching strategies, and improving student learning outcomes. Key factors influencing effectiveness include engaging and interactive training formats, knowledgeable facilitators, and collaborative opportunities among educators. Teachers also reported increased confidence in their teaching abilities and observed positive changes in student engagement. However, challenges such as scheduling constraints by limiting time for deep learning, causing cognitive overload, and reducing opportunities for follow-up and reflection. Also, the need for sustained institutional support were noted. The study concludes that PD programs significantly contribute to teacher effectiveness and professional growth. To optimize their impact, continuous mentorship, flexible program structures, and alignment with real classroom challenges should be prioritized.